ANALISIS DAYA SAING EKSPOR KOMODITAS UBI KAYU INDONESIA, THAILAND DAN VIETNAM DI PASAR DUNIA - Yudha, Eka Purna; Salsabila, Anisa; Haryati, Tantina (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Indonesia ranks third in cassava (cassava) exporters in global scale, after Thailand and Vietnam, more than 80% of cassava is exported to China. The productivity of cassava in Indonesia tends to increase, but the total volume of exports tends to decrease. This study focuses on describing the condition of the cassava timber export market trend to producing countries and then analyzes it comparatively in the global market and compares it with two other countries, namely Thailand and Vietnam. The data used is the 2014-2018 time series obtained from secondary data. This study was analyzed by RCA (Reveled Comparative Advantage). The results of research on the export volume of Indonesian cassava commodities in 2014-2018 to the main export destination countries, namely China, South Korea and Malaysia fluctuated and tended to decrease. The competitiveness of Indonesia's cassava commodity exports to China, South Korea and Vietnam can be seen from the results of the calculation of the RCA value which shows that Indonesian cassava does not have competitiveness and comparative advantage in China, South Korea and Malaysia. Although the RCA value of Indonesian cassava is low, the production value of Indonesian cassava is high. From the results of RCA calculations, Thailand and Vietnam have high competitiveness in cassava exports to destination countries, namely China, South Korea and Malaysia because they have an excess value of 1 .